Late Persian-Early Hellenistic Remains at Tel ͑Eton. (June 2015) - Faust, Avraham; Katz, Hayah; Eyall, Pirchia
Abstract : The paper deals with the finds from the Late Persian-Early Hellenistic period settlement unearthed at Tel ͑Eton. The settlement, which existed during the 4th and early 3rd centuries BCE, was comprised of a fort at the top of the mound and a large village that surrounded it. The article presents the architectural, ceramic and additional finds and discusses the possible circumstances involved in the establishment of the site in the 4th century BCE, after a settlement hiatus of some 300-350 years. It also examines the possible causes for its abandonment during the course of the 3rd century BCE.